2018
DOI: 10.1101/281485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional analysis of a hypomorphic allele shows that MMP14 catalytic activity is the prime determinant of the Winchester syndrome phenotype

Abstract: Winchester syndrome (WS, MIM #277950) is an extremely rare autosomal recessive skeletal dysplasia characterized by progressive joint destruction and osteolysis. To date, only one missense mutation in MMP14, encoding the membrane-bound matrix metalloprotease 14, has been reported in WS patients. Here, we report a novel hypomorphic MMP14 p.Arg111His (R111H) allele, associated with a mitigated form of WS. Functional analysis demonstrated that this mutation, in contrast to previously reported human and murine MMP1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…[78][79][80] We have previously reported that it can cause severe acne with hypertrophic scarring and thickened skin. 81 Mutations in MMP14 have been associated with WS via one mutation that decreases the membrane localization and another that disrupts the catalytic activity, resulting in impaired pro-MMP2 activation. 81,82 WS is part of a continuous clinical spectrum together with multicentric osteolysis, nodulosis and arthropathy (MONA) syndrome, Torg syndrome and nodulosisarthropathy-osteolysis (NAO) syndrome (MIM 259600).…”
Section: Winchester Syndrome (Mim 277950)mentioning
confidence: 99%
See 3 more Smart Citations
“…[78][79][80] We have previously reported that it can cause severe acne with hypertrophic scarring and thickened skin. 81 Mutations in MMP14 have been associated with WS via one mutation that decreases the membrane localization and another that disrupts the catalytic activity, resulting in impaired pro-MMP2 activation. 81,82 WS is part of a continuous clinical spectrum together with multicentric osteolysis, nodulosis and arthropathy (MONA) syndrome, Torg syndrome and nodulosisarthropathy-osteolysis (NAO) syndrome (MIM 259600).…”
Section: Winchester Syndrome (Mim 277950)mentioning
confidence: 99%
“…81 Mutations in MMP14 have been associated with WS via one mutation that decreases the membrane localization and another that disrupts the catalytic activity, resulting in impaired pro-MMP2 activation. 81,82 WS is part of a continuous clinical spectrum together with multicentric osteolysis, nodulosis and arthropathy (MONA) syndrome, Torg syndrome and nodulosisarthropathy-osteolysis (NAO) syndrome (MIM 259600). 81 Based on the identification of MMP2 gene mutations, MONA, Torg and NAO syndromes were originally thought to be distinct from WS, but they are now seen as allelic disorders due to overlapping mechanisms of action.…”
Section: Winchester Syndrome (Mim 277950)mentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, we found a novel homozygous missense MMP14 mutation in these patients (Wilson et al, ). We recently reported that it mostly likely represents a hypomorphic allele (De Vos et al, ).…”
Section: Introductionmentioning
confidence: 99%